2020
DOI: 10.5888/pcd17.190217
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cigarettes and E-Cigarettes and Dual Use Among Adult Employees in the US Workplace

Abstract: What is already known on this topic? US smoking rates have steadily declined over time, but e-cigarette use and dual use are becoming increasingly popular. Increased worksite evidencebased interventions are still needed for tobacco control. What is added by this report? Employment type, age, sex, race/ethnicity, education, and health care coverage were associated with e-cigarette use and dual cigarette and ecigarette use. Recent quit attempts were higher among dual users. Tobacco-product use varied by state. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…There were many more current e-cigarette users in the sample than in the general working adult population. 6 Given that those who vape were more likely to observe coworkers vaping, this oversample of e-cigarette users may have inflated the prevalence of observed workplace vaping and our results should not be interpreted as a precise estimate of workplace vaping. However, the oversample of users is likely to have led to an underestimate of the prevalence of negative attitudes about workplace vaping.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…There were many more current e-cigarette users in the sample than in the general working adult population. 6 Given that those who vape were more likely to observe coworkers vaping, this oversample of e-cigarette users may have inflated the prevalence of observed workplace vaping and our results should not be interpreted as a precise estimate of workplace vaping. However, the oversample of users is likely to have led to an underestimate of the prevalence of negative attitudes about workplace vaping.…”
Section: Discussionmentioning
confidence: 83%
“… 5 A recent study using a nationally representative sample found that vaping among working adults was higher than among adults in the United States generally. 6 The study found 4.8% of working adults were current e-cigarette users, and about half of those were dual users of e-cigarettes and combustible cigarettes. 6 Working adults who vape are also more likely to be younger, male, non-Hispanic white, to have less education, and to be without healthcare coverage than working adults who don’t use e-cigarettes or combustible cigarettes.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Recent prevalence data revealed that the adult users aged 25-44 years and aged 45-64 years had increased to 4.2% among adults aged 25-44 years and 2.1% among adults aged 45-64 years as per the National Health Interview Survey (NHIS) data in 2018 [1]. In the United States, the proportion of current E-Cigs users has increased to 4.8% of the adult population, and 2.3% of whom also use tobacco use (dual users), and 17.8% of whom are former users [2]. This study sought to assess and compare cardiovascular outcomes between E-Cigs users and tobacco smokers through a self-reported NHIS data questionnaire.…”
Section: Introductionmentioning
confidence: 99%